Genome-wide association and dissociation studies in Pantoea ananatis reveal potential virulence factors affecting Allium porrum and Allium fistulosum × Allium cepa hybrid - Myers, Brendon K.; Shin, Gi Yoon; Agarwal, Gaurav; Stice, Shaun P.; Gitaitis, Ronald D.; Kvitko, Brian H.; Dutta, Bhabesh (Frontiers in Microbiology, 2023)
Pantoea ananatis is a member of a Pantoea species complex that causes center rot of bulb onions (A. cepa) and also infects other Allium crops like leeks (Allium porrum), chives (A. schoenoprasum), bunching onion or Welsh onion (A. fistulosum), and garlic (A. sativum). We used phenotype-dependent genome-wide association (GWAS) and phenotype-independent gene-pair coincidence (GPC) analyses on a panel of diverse 92 P. ananatis strains, which were inoculated on A. porrum and A. fistulosum x A. cepa under greenhouse conditions. Phenotypic assays showed that, in general, these strains were more aggressive on A. fistulosum x A. cepa as opposed to A. porrum. Of the 92 strains, only six showed highly aggressive foliar lesions on A. porrum compared to A. fistulosum x A. cepa. Conversely, nine strains showed highly aggressive foliar lesions on A. fistulosum x A. cepa compared to A. porrum. These results indicate that there is an underlying genetic component that may drive host range in our P. ananatis samples. Based on GWAS for foliar pathogenicity, 835 genes were associated with P. ananatis’ pathogenicity on A. fistulosum x A. cepa whereas 243 genes were associated with bacterial pathogenicity on A. porrum. The ‘HiVir’ as well as the alt gene clusters were identified among these genes. Besides the ‘HiVir’ and alt gene clusters that are known to contribute to pathogenicity and virulence from previous studies, genes annotated with functions related to stress responses, a potential toxin-antitoxin system, flagellar-motility, quorum sensing, and a previously described phosphonoglycan biosynthesis (pgb) cluster were identified. Further a comparative genomics analysis was performed on five P. ananatis strains that were differentially pathogenic on A. porrum or A. fistulosum x A. cepa. Here, we found a putative type III secretion system, and several other genes that occurred on both GWAS outputs of both Allium hosts. Further, we also demonstrated utilizing mutational analysis that the pepM gene in the ‘HiVir’ cluster but not the ‘pgb’ cluster is important for P. ananatis’ pathogenicity on A. fistulosum x A. cepa and A. porrum.